Bifacial Color‐Tunable Transparent Photovoltaics for Application as Building‐Integrated Photovoltaics. Issue 8 (8th August 2021) - Kim, Sangho; Yi, Junsin; Kim, Joondong
Abstract : Transparent Photovoltaics In article number 2100162, Sangho Kim, Junsin Yi, and Joondong Kim demonstrate the bifacial colortunable transparent photovoltaics (TPVs) for building integration. High‐power output was given from a large area (16 cm 2 ) TPV device. In the merit of an all‐transparent feature, TPVs generate power in both (front and back) directions and modulate colors on‐demand. Power can be obtained invisibly from TPVs on glass and color‐tuned surfaces.